Effect of sunflower oil supplementation as unsaturated fatty acid source on rumen fermentability and performance of lactating Garut ewes - Khotijah, L.; Pandiangan, E. I.; Astuti, D. A.; Wiryawan, K. G. (Journal of the Indonesian Tropical Animal Agriculture, 2017)
The study was aimed to evaluate the increasing levels of ration energy, with fat-rich unsaturated fatty acids from sunflower oil on the nutrient intake, rumen fermentability and performance of ewes. The experiment used fifteen ewes of 1.5 years old, primiparous, caged individually with their lambs and conducted three treatments and five replications from a completely randomized designed. Those treatments included R1= ration with 0% sunflower oil addition, R2= ration with 4%sunflower oil addition, R3= ration with 6% sunflower oil addition. The variables consisted of dry matter intake, nutrients, ewes performances (birth weight, weaning weight, decreased of body weight), total and partial VFA, the ratio of acetate: propionate, methane production, protozoa and bacterial population. Data were analyzed statistically and descriptively. The results showed that the treatments did not influence dry matter intake and nutrients,. rumen fermentability and ewes performances. Although the treatments increased (P<0.01) fatconsumption and reduced shrinkage of body weight. It can be concluded that the adding sunflower oil as the resource of unsaturated fatty acids up to 6% of the ration was not negatively affected the fermentability of rumen, moreover can improve ewes body condition and, accelerated body weight recovery